By pure luck : a memoir - Igielnik, Fela, 1927-2009.; Short, Curtiss (College Station, TX : Virtualbookworm.com Publishing Inc., 2012)
This remarkable story tells how Fela Igielnik survived life in the Warsaw ghetto and the brutality of World War II. But more than that, it reveals the possibility of transforming even the darkest of experiences -- starvation, forced labor and marches, institutionalized hatred -- into opportunities for furthering education and understanding.
Record updated by Marcive processing 21 June 2024
Keywords: Igielnik, Fela, -- 1927-2009.; Jews -- Poland -- Warsaw -- Biography; Holocaust survivors -- Poland -- Biography; Holocaust survivors -- Germany -- Biography; Holocaust, Jewish (1939-1945) -- Personal narratives; Skarżysko-Kamienna (Concentration camp); Getto warszawskie (Warsaw, Poland) -- Biography; Autobiographies; Personal narratives